2022
DOI: 10.3390/bs12020056
|View full text |Cite
|
Sign up to set email alerts
|

Why and When Do Employees Hide Their Knowledge?

Abstract: This study establishes a theoretical and integrative framework for analyzing the relationship between knowledge hiding and task performance. The existing literature indicates that knowledge hiding is prominent in service sector firms and impedes knowledge transfer. However, the potential determinants and consequences have not been extensively investigated. The objectives of this study are threefold: First, examining the effect of distrust and the complexity of knowledge on knowledge hiding. Second, examining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Existing research evidence suggests that knowledge hiding reduces individual and team creativity, reduces individuals' innovative work behavior, and increases voluntary turnover. Although organizations implement various incentives to promote knowledge sharing, knowledge-sharing initiatives do not necessarily eliminate knowledge hiding because there are different drivers of knowledge hiding; e.g., from a leadership perspective, Donate Mario J and other scholars found that knowledge-oriented leadership has a positive and strong direct impact on knowledge hiding [ 29 ]; Agarwal Upasna et al confirmed that ethical leadership can reduce the occurrence of knowledge hiding behaviors [ 30 ]; Changyu Wang and other scholars confirmed that the abusive management implemented by leaders has a positive impact on subordinates' knowledge hiding behaviors [ 31 ]; Yuan Ling et al verified that the U-type curve relationship between humble leadership and employee knowledge hiding was significant [ 32 ]; from the perspective of knowledge attributes, scholars such as Sulistiawan Jovi have confirmed that knowledge complexity is also an important factor affecting employees' knowledge hiding; from the perspective of individual characteristics, Soral Prakriti and others believe that the dark personality traits of superiors will enhance the knowledge hiding behaviors of subordinates [ 33 ]; Zoe Geofroy and Max Evans believe that employees with high emotional intelligence are less likely to hide their knowledge [ 34 ]; from the perspective of the organizational atmosphere, Oubrich Mourad et al's studies have confirmed that organizational equity reduces the occurrence of knowledge hiding behavior within organizations [ 35 ]; Li Hao et al have verified that defense orientation has a promoting effect on knowledge hiding in enterprises, performance atmosphere can enhance the impact of defense orientation on knowledge hiding, and the adjustment effect of weak performance atmosphere and strong performance atmosphere changes with the change in defense orientation [ 36 ]; from the perspective of interpersonal relationships, scholars such as Sulistiawan Jovi have confirmed that interpersonal distrust is a key factor in predicting employee knowledge hiding [ 37 ]; Cheng and Bao explored the promotion of negative rumors among employees in knowledge hiding [ 38 ]; Cegarra-Navarro Juan-Gabriel and other scholars found that defensive practices produced by interpersonal relationship were positively correlated with knowledge hiding [ 39 ]; Alam Tahira and other scholars found that relationship conflict positively affects knowledge hiding [ 40 ]; Sidra Riaz et al studies have confirmed that workplace exclusion positively influences knowledge hiding behavior [ 41 ]; Connelly and Zweig will be the interpersonal deterioration [ 42 ]. The organization network of the individual cannot be ignored.…”
Section: Concept Definition and Literature Reviewmentioning
confidence: 99%
“…Existing research evidence suggests that knowledge hiding reduces individual and team creativity, reduces individuals' innovative work behavior, and increases voluntary turnover. Although organizations implement various incentives to promote knowledge sharing, knowledge-sharing initiatives do not necessarily eliminate knowledge hiding because there are different drivers of knowledge hiding; e.g., from a leadership perspective, Donate Mario J and other scholars found that knowledge-oriented leadership has a positive and strong direct impact on knowledge hiding [ 29 ]; Agarwal Upasna et al confirmed that ethical leadership can reduce the occurrence of knowledge hiding behaviors [ 30 ]; Changyu Wang and other scholars confirmed that the abusive management implemented by leaders has a positive impact on subordinates' knowledge hiding behaviors [ 31 ]; Yuan Ling et al verified that the U-type curve relationship between humble leadership and employee knowledge hiding was significant [ 32 ]; from the perspective of knowledge attributes, scholars such as Sulistiawan Jovi have confirmed that knowledge complexity is also an important factor affecting employees' knowledge hiding; from the perspective of individual characteristics, Soral Prakriti and others believe that the dark personality traits of superiors will enhance the knowledge hiding behaviors of subordinates [ 33 ]; Zoe Geofroy and Max Evans believe that employees with high emotional intelligence are less likely to hide their knowledge [ 34 ]; from the perspective of the organizational atmosphere, Oubrich Mourad et al's studies have confirmed that organizational equity reduces the occurrence of knowledge hiding behavior within organizations [ 35 ]; Li Hao et al have verified that defense orientation has a promoting effect on knowledge hiding in enterprises, performance atmosphere can enhance the impact of defense orientation on knowledge hiding, and the adjustment effect of weak performance atmosphere and strong performance atmosphere changes with the change in defense orientation [ 36 ]; from the perspective of interpersonal relationships, scholars such as Sulistiawan Jovi have confirmed that interpersonal distrust is a key factor in predicting employee knowledge hiding [ 37 ]; Cheng and Bao explored the promotion of negative rumors among employees in knowledge hiding [ 38 ]; Cegarra-Navarro Juan-Gabriel and other scholars found that defensive practices produced by interpersonal relationship were positively correlated with knowledge hiding [ 39 ]; Alam Tahira and other scholars found that relationship conflict positively affects knowledge hiding [ 40 ]; Sidra Riaz et al studies have confirmed that workplace exclusion positively influences knowledge hiding behavior [ 41 ]; Connelly and Zweig will be the interpersonal deterioration [ 42 ]. The organization network of the individual cannot be ignored.…”
Section: Concept Definition and Literature Reviewmentioning
confidence: 99%
“…To test the proposed hypotheses, we analyzed the path coefficients. We followed the recommendation from Sulistiawan et al. (2022) and assessed the proposed hypotheses' strength using bootstrapping with 5000 subsamples.…”
Section: Resultsmentioning
confidence: 99%
“…The cut-off value for the composite reliability is higher than 0.70 (Hair et al, 2016;Moslehpour et al, 2019). Last, we evaluate the discriminant validity using both the Fornell -Larcker criterion and the Heterotrait -Monotrait correlations (HTMT) (Sulistiawan et al, 2022). Table 3 shows the Fornell -Larcker criterion.…”
Section: Assessment For the Measurement Modelmentioning
confidence: 99%
“…To evaluate our proposed hypotheses, we assessed the path coefficient. We employed bootstrapping technique in PLS with 5,000 subsamples to assess the significance of the hypotheses (Hui-Wen Chuah et al, 2022;Sulistiawan et al, 2022). The summary of hypotheses testing is in table 5.…”
Section: Direct Effectmentioning
confidence: 99%